Pesticide Biotransformation and Disposition - Ernest Hodgson, ed; Ernest Hodgson, ed (New York Academic Press, 2012)
This book emphasizes metabolism in non-target species, such as experimental animals and humans, and includes four new chapters and thoroughly updated material.
Absorption Pesticide Excretion Biotrnsformation
Keywords: Absorption; Pesticide Excretion; Biotrnsformation